E-Assessment and Academic Integrity in Nigeria - Ezeabasili, Ifeoma Ethel (Current Overview on Science and Technology Research Vol. 6, 2022)
E-assessment refers to the use of information and communication technology to evaluate students learning .It involves the use of computer to administer test and grade students performances. The use of e-assessment is applicable to both developed and developing economies. It is used in elementary school, distance learning and professional certification exams. The application is aimed at reducing the stress and challenges that comes with the traditional pen and paper. In spite of all these, there is a widespread perception that the departure from academic integrity is on the rise due to the introduction of information and communication technology into the classroom and the popularity of online classes, which have created new opportunities for ‘e-cheating’ The National Open University of Nigeria since its inception in 2002, has examined their students using the traditional method of pen and paper, however, the process has been saddled with a lot of problems leading to the inability of the university to release students results on time , the inability of some students to graduate in recorded time. These problems led to the introduction of e-assessment into National Open University of Nigeria. This chapter examines the antecedents that led to the introduction of e-assessment in Nigeria higher institutions of learning. It presented some basic concepts of e-assessment; origin and Development of E-assessment; Functions and advantages of e-assessment; constraints to E-assessment in Nigeria. It also discussed the origin of e-assessment and academic integrity in Nigeria; Origin and Development of Academic Integrity; e-assessment and Academic dishonesty. The chapter posits that the relationship between e-assessment and Academic Integrity is that E-assessment enhances Academic integrity, and concluded that e-assessment was introduced into Nigerian in 2010 to ease learning process, eliminate examination malpractices, accelerate the release of student’s results and promote academic integrity. However, the realization of these objectives in Nigeria is far-fetched due to some constraints like the human interferences, computer technology illiteracy among students in tertiary institutions, high cost of procuring and installing the gadgets required for e-learning. Despite all these challenges, e-assessment has impacted greatly on academic Integrity in Nigeria.